Li-ion conductor and method for producing same
A novel Li ion conductor composition, incorporating specific metal elements and molar ratios, addresses the challenges of safety, stability, and energy density in Li-ion batteries by enhancing ionic conductivity and sinterability.
Patent Information
- Application Number
- JP2022504424
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-05
- Filing Date
- 2021-03-03
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2041-03-03
AI Technical Summary
Existing Li-ion secondary batteries face challenges in achieving high safety, long-term cycle stability, and high energy density, particularly in all-solid-state batteries using solid electrolytes.
A Li ion conductor with a novel composition, including at least one species selected from Ga, V, and Al, and Li, La, and O, where part of the Li site may be substituted with metal element D, part of the La site with metal element E, and part of Ga, V, and Al with metal element J, with specific molar ratios and calcination processes to enhance ionic conductivity.
The Li ion conductor exhibits good Li ion conduction with improved bulk ionic conductivity and sinterability, leading to enhanced overall ionic conductivity and stability, which addresses the limitations of existing Li-ion battery technologies.
Smart Images

Figure 0007665590000004 
Figure 0007665590000005 
Figure 0007665590000001
Abstract
Description
Technical Field
[0001] The present invention relates to a Li ion conductor and a method for producing the same.
Background Art
[0002] Research and development of Li ion secondary batteries are actively carried out in portable devices, hybrid vehicles, electric vehicles, and household power storage applications. The Li ion secondary batteries used in these fields are required to have high safety, long-term cycle stability, high energy density, etc.
[0003] Among them, all-solid-state batteries using solid electrolytes have attracted attention due to their high safety. For example, in Patent Document 1, as a garnet-type oxide having lithium ion conductivity, Li 7+X+Y La 3-X A X Zr 2-Y T Y O 12 (wherein element A is one or more elements selected from the group consisting of Ba, Sr, Ca, Mg, and Y, element T is one or more elements selected from the group consisting of Sc, Ti, V, Y, Nb, Hf, Ta, Al, Si, Ga, and Ge, and 0 < X ≦ 1, 0 ≦ Y ≦ 1, and X < Y are satisfied) is disclosed.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0005] An object of the present invention is to provide a Li ion conductor having a composition different from the conventional ones.
Means for Solving the Problems
[0006] The present invention, which has achieved the above object, is as follows. [1] A Li ion conductor containing at least one selected from the group Q consisting of Ga, V, and Al, and Li, La, and O, in which a part of the Li sites may be substituted with a metal element D, a part of the La sites may be substituted with a metal element E, and a part of the Ga, V, and Al sites may be substituted with a metal element J; the amount of Li is in a molar ratio of 8.1 / 5 or more and 9.5 / 5 or less to the total amount of La, the element E, Ga, V, Al, and the element J; A Li-ion conductor, characterized in that the molar ratio of the total amount of Ga, V and Al to the total amount of La and the element E is 1.1 / 3 or more and 2 / 3 or less. [2] The Li ion conductor according to [1], having a lattice constant of 12.95 Å or more. [3] Formula (1): (Li p1 D p2 )(La p3 E p4 )(Q p5 J p6 )O 12 The Li ion conductor according to [1] or [2], wherein In the above formula (1), Q is at least one element selected from the group consisting of Ga, V, and Al, D is a metal element substituting a part of the Li site, E is a metal element substituting a part of the La site, and J is a metal element substituting a part of the Q site, p1, p3, and p5 are values greater than 0, p2, p4, and p6 may be 0, p1 / (p3+p4+p5+p6) is 8.1 / 5 or more and 9.5 / 5 or less, p5 / (p3+p4) is 1.1 / 3 or more and 2 / 3 or less, and (valence of Li)×p1+(valence of the element D)×p2+(valence of La)×p3+(valence of the element E)×p4+(valence of the element Q)×p5+(valence of the metal element J)×p6=24 is satisfied. [4] The Li ion conductor according to [3], wherein p1 is 8.1 or more and 9.5 or less, p2, p4, and p6 are all 0 or more and 0.5 or less, p3 is 2.5 or more and 3 or less, and p5 is 1.5 or more and 2 or less. [5] Formula (2): Lix1 La x2 (Ga, V, Al) x3 Hf x4 Sr x5 Zr x6 O 12 A Li-ion conductor represented by the formula: In formula (2), x1 is 8.1 or more and 9.5 or less, x2 is 2.5 or more and 3 or less, x3 is 1.5 or more and 2 or less, x4, x5, and x6 are each independently 0 or more and 0.5 or less, and x1+x2×3+x3×3+x4×4+x5×2+x6×4=24 is satisfied, and (Ga, V, Al) means that at least one of Ga, V, and Al is contained, and when multiple types are contained, x3 means the total amount of the multiple types. [6] A raw material mixture including at least one selected from the group Q consisting of Ga, V, and Al, and at least one of a metal element D containing Li and La and capable of substituting a part of the Li site in the crystal structure, a metal element E capable of substituting a part of the La site in the crystal structure, and a metal element J capable of substituting a part of the Ga, V, and Al sites in the crystal structure, A method for producing a Li ion conductor, comprising firing a raw material mixture at 1100°C or higher, the raw material mixture including a molar ratio of Li to the total amount of La, the element E, Ga, V, Al and the element J of 8.1 / 5 or more and 9.5 / 5 or less, and a molar ratio of the total amount of Ga, V and Al to the total amount of La and the element E of 1.1 / 3 or more and 2 / 3 or less. [7] The molar ratio of each metal element in the raw material mixture is expressed by the formula (1): (Li p1 D p2 )(La p3 E p4 )(Q p5 J p6 )O 12 The method according to [6], wherein the compound is represented by a stoichiometric ratio. In the above formula (1), Q is at least one element selected from the group consisting of Ga, V, and Al, D is a metal element substituting a part of the Li site, E is a metal element substituting a part of the La site, and J is a metal element substituting a part of the Q site, p1, p3, and p5 are values greater than 0, p2, p4, and p6 may be 0, p1 / (p3+p4+p5+p6) is 8.1 / 5 or more and 9.5 / 5 or less, p5 / (p3+p4) is 1.1 / 3 or more and 2 / 3 or less, and (valence of Li)×p1+(valence of the element D)×p2+(valence of La)×p3+(valence of the element E)×p4+(valence of the element Q)×p5+(valence of the metal element J)×p6=24 is satisfied. Effect of the Invention
[0007] According to the present invention, it is possible to provide a Li-ion conductor having a composition that has not been known before. [Brief description of the drawings]
[0008] [Figure 1] 1 is a drawing-substitute photograph showing a cross-sectional SEM image of a sintered pellet obtained in an example. [Diagram 2] 2 is an XRD diffraction chart obtained by analyzing the crystal structure of the sintered pellet obtained in the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present inventors have found that good Li-ion conduction is achieved with the following composition, which is different from conventionally known Li-ion conductors. The Li-ion conductor of the present invention is a Li-ion conductor containing at least one selected from group Q consisting of Ga, V, and Al, and Li, La, and O, in which a part of the Li site may be substituted with a metal element D, a part of the La site may be substituted with a metal element E, and a part of the Ga, V, and Al sites may be substituted with a metal element J, (i) the amount of Li is 8.1 / 5 or more and 9.5 / 5 or less in molar ratio to the total amount of La, the element E, Ga, V, Al, and the element J, and (ii) the total amount of Ga, V, and Al is 1.1 / 3 or more and 2 / 3 or less in molar ratio to the total amount of La and the element E.
[0010] The Li-ion conductor of the present invention mainly comprises at least one element selected from group Q consisting of Ga, V, and Al, and Li, La, and O. The Li content is greater than or equal to a predetermined amount (above (i)), and the total content of Ga, V, and Al is greater than or equal to a value that ... 12 The oxide having the basic composition (above (ii)) is characterized in that it contains these elements in amounts greater than those contained in the oxide having the basic composition (above (ii)).
[0011] The amount of Li is 8.1 / 5 or more in terms of molar ratio to the total amount of La, the element E, Ga, V, Al, and the element J, and good Li ion conduction can be realized. The molar ratio is preferably 8.5 / 5 or more, more preferably 8.7 / 5 or more, and even more preferably 8.9 / 5 or more. The upper limit of the molar ratio is 9.5 / 5 or less, and may be 9.4 / 5 or less, or may be 9.3 / 5 or less.
[0012] The total amount of Ga, V and Al is 1.1 / 3 or more in terms of molar ratio to the total amount of La and the element E. The molar ratio is preferably 1.3 / 3 or more, more preferably 1.5 / 3 or more, and even more preferably 1.7 / 3 or more.
[0013] The metal element D is an element capable of substituting a part of the Li site, for example, Al, Sr, Ca, Ba, Mg, Hf, etc., and Hf is preferred. The metal element E is an element capable of substituting a part of the La site, for example, Zn, Ca, Mg, Ba, Sr, etc., and Sr is preferred. The metal element J is an element capable of substituting a part of the Ga, V or Al site, for example, Te, Ta, Nb, Zr, etc., and Zr is preferred. The metal elements D, E, and J are expected to have at least one of the following effects: increasing the bulk ion conductivity (i.e., ion conduction within the crystal) by substituting each site of other elements in the crystal structure of the Li ion conductor and optimizing the Li carrier concentration; and improving the sinterability to improve the bonding state of the particle interface and form a dense sintered body. In particular, it is preferable that the Li ion conductor contains at least two of Hf (metal element D), Sr (metal element E) and Zr (metal element J), and the Li carrier concentration is optimized to improve the ionic conductivity of the bulk, and the sintering is promoted to obtain a dense sintered body, and the overall ionic conductivity of the bulk and the grain boundary is improved. In particular, it is preferable that the Li ion conductor contains Zr (metal element J) and at least one of Hf (metal element D) and Sr (metal element E), which is advantageous for improving the overall ionic conductivity. It is also preferable that the Li ion conductor contains Sr (metal element E) and at least one of Hf (metal element D) and Zr (metal element J). In addition, it is more preferable that the Li ion conductor of the present invention contains all of Sr, Hf and Zr, and by doing so, the ionic conductivity can be further improved.
[0014] It is also preferable that Al, Sr, Ca, Ba, Mg, Hf, Zn, Te, Ta, Nb, and Zr listed as preferred elements of the above elements D, E, and J substitute element sites as described above, respectively. However, as long as at least one element selected from group Q consisting of Ga, V, and Al is included in the Li ion conductor together with Li, La, and O, it may substitute sites other than those described above.
[0015] The elements contained in the Li-ion conductor of the present invention are preferably contained in a molar ratio that keeps the Li-ion conductor electrically neutral. Of the elements of group Q, it is preferable that at least Ga is contained, and it is preferable that the element of group Q is Ga alone.
[0016] The Li-ion conductor of the present invention is usually crystalline, and examples of the crystal structure of the main phase include a garnet structure and a perovskite structure, and the main phase is preferably a garnet structure. The main phase refers to a structure to which the peak with the highest intensity in the X-ray diffraction spectrum belongs. When the Li-ion conductor of the present invention is crystalline, the lattice constant is preferably 12.95 Å or more, and a large lattice constant tends to improve the Li-ion conductivity. The lattice constant is more preferably 12.97 Å or more, and even more preferably 13.00 Å or more, and may be 13.12 Å or less.
[0017] The Li-ion conductor of the present invention is preferably represented by the following formula (1). Formula (1): (Li p1 D p2 )(La p3 E p4 )(Q p5 J p6 )O 12 In the above formula (1), Q is at least one element selected from the group consisting of Ga, V, and Al, and D, E, and J are synonymous with the above-mentioned metal elements D, E, and J, respectively. In addition, p1, p3, and p5 are values greater than 0, p2, p4, and p6 may be 0 (at least one of p2, p4, and p6 may be 0), p1 / (p3+p4+p5+p6) is 8.1 / 5 or more and 9.5 / 5 or less, p5 / (p3+p4) is 1.1 / 3 or more and 2 / 3 or less, and satisfies (valence of Li)×p1+(valence of the element D)×p2+(valence of La)×p3+(valence of the element E)×p4+(valence of the element Q)×p5+(valence of the metal element J)×p6=24.
[0018] For D, E, and J in formula (1), the descriptions, including the preferred ranges, of the metal elements D, E, and J can be referred to. For the element Q, the descriptions of the group Q can be referred to.
[0019] In addition, the value of p1 / (p3+p4+p5+p6) corresponds to the molar ratio of Li to the total amount of La, the element E, Ga, V, Al and the element J described above, and the value of p5 / (p3+p4) corresponds to the molar ratio of the total amount of Ga, V and Al to the total amount of La and the element E described above. Therefore, the above-mentioned ranges can be referred to for all preferred ranges.
[0020] The values of p1 to p6 are not limited as long as they satisfy the above relational expressions, but preferred values are as follows.
[0021] p1 is preferably 8.1 or more, more preferably 8.5 or more, and further preferably 8.7 or more, and may be 9.5 or less, 9.4 or less, or 9.3 or less.
[0022] p2 is 0 or more, preferably 0.01 or more, more preferably 0.05 or more, and even more preferably 0.075 or more, and is preferably 0.5 or less, more preferably 0.2 or less, and even more preferably 0.1 or less.
[0023] p3 is preferably 2.5 or more, more preferably 2.7 or more, and even more preferably 2.8 or more, and is preferably 3 or less, more preferably 2.95 or less, and even more preferably 2.9 or less.
[0024] p4 is 0 or more, preferably 0.05 or more, more preferably 0.1 or more, and is preferably 0.5 or less, more preferably 0.3 or less, and further preferably 0.2 or less.
[0025] p5 is preferably 1.5 or more, more preferably 1.7 or more, and is preferably 2 or less, more preferably 1.9 or less.
[0026] p6 is 0 or more, preferably 0.05 or more, more preferably 0.1 or more, and is preferably 0.5 or less, more preferably 0.3 or less.
[0027] It is particularly preferable that p1 is 8.1 or more and 9.5 or less, p2, p4, and p6 are all 0 or more and 0.5 or less, p3 is 2.5 or more and 3 or less, and p5 is 1.5 or more and 2 or less.
[0028] The Li ion conductor of the present invention preferably contains at least one selected from the group Q consisting of Ga, V, and Al, Li, La, and O, and at least one of Hf, Sr, and Zr among the above-mentioned Al, Sr, Ca, Ba, Mg, Hf, Zn, Te, Ta, Nb, and Zr as necessary, and has a specific composition. More specifically, the Li ion conductor of the present invention preferably has a specific composition represented by the formula (2): Li x1 La x2 (Ga, V, Al) x3 Hf x4 Sr x5 Zr x6 O 12 The present invention also includes a Li ion conductor represented by the following formula: In formula (2), x1 is 8.1 or more and 9.5 or less, x2 is 2.5 or more and 3 or less, x3 is 1.5 or more and 2 or less, x4, x5 and x6 are each independently 0 or more and 0.5 or less, and satisfy x1+x2×3+x3×3+x4×4+x5×2+x6×4=24, (Ga, V, Al) means that at least one of Ga, V and Al is contained, and when multiple types are contained, x3 means the total amount of the multiple types. In formula (2), when at least one of Hf, Sr and Zr is contained, its existence form is not particularly limited, and it may substitute a part of the site of any of Li, La, Ga, V and Al. In formula (2), it is also preferable that x1 / (x2+x5+x3+x6) is 8.1 / 5 or more and 9.5 / 5 or less, and x3 / (x2+x5) is 1.1 / 3 or more and 2 / 3 or less (requirement 2-1). In formula (2), it is also preferable that x1 is 8.5 to 9, x2 is 2.9 to 3, x3 is 1.9 to 2, x4 is 0 to 0.1, x5 is 0 to 0.1, and x6 is 0 to 0.1 (requirement 2-2). Furthermore, when formula (2) is Li x1 La x2 Ga x3 Hf x4 Sr x5 Zr x6 O 12 It is also preferable that the formula (2) satisfies the above requirements (2-1) and (2-2), and it is further preferable that the formula (2) satisfies all of the requirements (2-1) to (2-3).
[0029] When multiple (k) elements are included as the element D, the valences of the multiple elements D are D i , the molar ratio of each element D in the total elements D is n i Then, the valence of element D is calculated by the following formula: When multiple elements are included as element E and element J, the valence of element E and the valence of element J may be calculated in the same manner.
number
[0030] The Li-ion conductor of the present invention has an ionic conductivity σ total But for example, 1.0×10 -6 S / cm or more, preferably 1.0×10 -5 S / cm or more, more preferably 1.0×10 -4 S / cm or more, and more preferably 2.0×10 -4 S / cm or more, and although there is no upper limit, it is 7.0×10 -4 S / cm or less, or 6.0×10 -4 The activation energy E measured by the method of the examples described later may be less than 1.5 S / cm. a (eV) is, for example, 0.45 eV or less, preferably 0.40 eV or less, and more preferably 0.37 eV or less, and the lower limit is not particularly limited, but may be, for example, 0.20 eV or more.
[0031] The Li-ion conductor of the present invention can be obtained by firing a raw material mixture containing at least one element selected from the group consisting of Ga, V, and Al, Li, La, and, as necessary, at least one of a metal element D capable of substituting a portion of the Li site in the crystal structure, a metal element E capable of substituting a portion of the La site in the crystal structure, and a metal element J capable of substituting a portion of the Ga, V, and Al sites in the crystal structure, at 1100°C or higher.
[0032] In the raw material mixture, the molar ratio of Li to the total amount of La, the element E, Ga, V, Al and the element J, and the molar ratio of the total amount of Ga, V and Al to the total amount of La and the element E are the same as those in the Li-ion conductor of the present invention described above. In a preferred embodiment, the molar ratio of each metal element in the raw material mixture is the stoichiometric ratio in the compound represented by the above formula (1), and all of the contents related to the above formula (1) described as a preferred embodiment of the Li-ion conductor of the present invention can be referred to.
[0033] As the raw materials of each element (other than O) constituting the Li ion conductor of the present invention, powders such as oxide, carbonate, hydroxide, chloride, and alkoxide of each metal element (i.e., Li, La, Ga, V, Al, element D, element E, and element J) can be used. The Li source powder is preferably Li oxide or Li carbonate, the La source powder is preferably La oxide or La hydroxide, and Ga, V, Al, element D, element E, and element J are all preferably oxides, carbonates, or hydroxides (particularly oxides or carbonates). It is more preferable that each of the raw materials is an oxide powder of each metal.
[0034] It is preferable to adjust the BET specific surface area of the raw material powder of each element. For example, the La source powder (especially La2O3) is 5 to 15 m 2 / g, Li source powder (especially Li2O) is 5 to 10m 2 / g, Ga source powder (especially Ga2O3) is 5 to 15m 2 / g, Zr source powder (especially ZrO2) is 15 to 20 m 2 It is preferable that the ratio is set to / g.
[0035] The firing of the raw material mixture at 1100°C or higher preferably includes a first firing step at 1100°C or higher in air, and a second firing step at 1100°C or higher in an inert gas atmosphere after the first firing step. In the first firing, the raw material mixture is molded under a pressure of, for example, 150 to 400 MPa (preferably 188 to 375 MPa), and the resulting molded body (first molded body) is preferably fired at 1100° C. or higher for 8 to 15 hours. The firing may be performed in the air. In the second firing, after the first firing, firing is preferably performed in an inert gas atmosphere such as dry nitrogen gas or argon gas at 1100° C. or higher (preferably 1200° C. or higher) for 3 to 30 hours (preferably 5 to 25 hours). When the raw material mixture is formed into a molded body and then fired in the first firing, it is preferable that the first molded body after the first firing is pulverized before being subjected to the second firing, and the powder obtained by pulverization is again molded at a pressure of about 150 to 400 MPa (preferably 188 to 375 MPa) to obtain a second molded body, and the second molded body is then subjected to the second firing. The first firing temperature is preferably 1200° C. or lower, the second firing temperature is preferably 1300° C. or lower, and the second firing temperature is preferably higher than the first firing temperature.
[0036] The weighing of the raw material mixture and the shaping in the first calcination are preferably carried out in an environment with reduced moisture, and both are preferably carried out in an environment (such as a glove box or dry room) with a dew point value of -120°C to -40°C (preferably -100°C to -50°C). The pulverization in the preferred embodiment of the second calcination is also preferably carried out in an environment with reduced moisture similar to that described above. Furthermore, the second calcination is also preferably carried out in an environment with reduced moisture, and a dry inert gas such as dry nitrogen with a dew point value of -80°C to -40°C can be used, and the flow rate of the inert gas may be, for example, 1 to 5 L / min.
[0037] This application claims the benefit of priority based on Japanese Patent Application No. 2020-038111, filed on March 5, 2020. The entire contents of the specification of Japanese Patent Application No. 2020-038111, filed on March 5, 2020, are incorporated by reference into this application. EXAMPLES
[0038] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and can of course be modified within the scope of the above and below-mentioned aims, and all such modifications are within the technical scope of the present invention.
[0039] Example 1-1 Li2O (manufactured by Kojundo Kagaku Co., Ltd., purity: 99%, specific surface area S w :8.4m2 / g, specific surface area diameter d BET :355nm), La2O3 (manufactured by Kojundo Kagaku Co., Ltd., purity: 99.9%, specific surface area S w :11.5m 2 / g, specific surface area diameter d BET :80nm), Ga2O3 (manufactured by Kojundo Kagaku Co., Ltd., purity: 99.99%, specific surface area S w :10.4m 2 / g, specific surface area diameter d BET The powders (diameter: 90 nm) were placed in a glove box (dew point: -98°C) and the composition of the resulting composite metal oxide was Li9La3Ga2O 12 A total of 5 g was weighed out at the stoichiometric ratio of 10 ...
[0040] Examples 1-2 to 1-10, Example 2-1, Examples 3-1 to 3-3 Sintered pellets were obtained in the same manner as in Example 1-1, except that the composition of the composite metal oxide and the firing time were as shown in Tables 1 and 2. In the examples containing Hf, HfO2 was used as the Hf source, in the examples containing Sr, SrCO3 was used as the Sr source, and in the examples containing Zr, ZrO2 (BET specific surface area of 18.4 m) was used as the Zr source. 2 The total amount of the raw material mixture was 5 g in each case, the same as in Example 1-1.
[0041] Both sides of the sintered pellet obtained in the above example were polished and Au was sputtered to form an electrode with a diameter of 8 mm. The sintered pellet sample with the electrode formed was set in an all-solid-state battery evaluation cell manufactured by Hohsen Co., Ltd. and connected to a potentiogalvanometer. Impedance measurements were performed in the temperature range from room temperature to 100°C to evaluate the Li ion conductivity. When the ion conductivity evaluated by impedance measurement can be divided into contributions from the bulk crystal and from the grain boundary, the total conductivity σ Total (S / cm), along with σ corresponding to the bulk crystalline portion Bulk The values of ionic conductivity (S / cm) at each temperature are also shown. Furthermore, the activation energy E a The ionic conductivity (eV) was calculated. The results are shown in Tables 1 and 2. Note that the ionic conductivity of Example 3-2 is the value at 75° C., the ionic conductivity of Example 3-3 is the value at 50° C., and the ionic conductivity of the other examples is the value at 25° C.
[0042] The lattice constants shown in Table 1 were measured as follows. The pellet sintered body was pulverized in a mortar in a glove box, and the crystal structure was analyzed using a Bruker XRD (X-ray Diffraction analysis) device. The lattice constant was calculated by determining the interplanar spacing d value from the (400) plane peak of the obtained X-ray diffraction peaks using the following formula. 2dSinθ=nλ (1) 1 / d 2 =(h 2 +k 2 +l 2 ) / a 2 (2) d: Plane spacing, a: Lattice constant
[0043] [Table 1]
[0044] [Table 2]
[0045] Tables 1 and 2 show that good Li-ion conductivity was achieved in compounds with novel compositions different from conventional ones.
[0046] In addition, cross-sectional SEM images of the sintered pellets obtained in Examples 1-6 and 1-8 are shown in Figure 1. Figure 1(a) shows Example 1-6, and Figure 1(b) shows Example 1-8. Example 1-6, which contains Zr together with Sr, and Example 1-8, which contains Hf and Zr together with Sr, show improved sintering characteristics, with many areas where the interfaces between particles have disappeared, resulting in good Li-ion conductivity.
[0047] Furthermore, the results of XRD analysis of the sintered pellets obtained in Examples 1-8 to 1-10 are shown in Figure 2. It was found that the main phase in all of Examples 1-8 to 1-10 was a garnet structure.
Claims
1. A Li ion conductor containing at least one element selected from the group Q consisting of Ga, V, and Al, and Li, La, and O, and represented by formula (1): (Li p1 D p2 ) (La p3 E p4 ) (Q p5 J p6 ) O 12 . In the above formula (1), Q is at least one element selected from the group consisting of Ga, V, and Al, D is a metal element that substitutes a part of the Li site, E is a metal element that substitutes a part of the La site, and J is a metal element that substitutes a part of the Q site. p1, p3, and p5 are values greater than 0, p2, p4, and p6 may be 0, p1 / (p3+p4+p5+p6) is 8.1 / 5 or more and 9.5 / 5 or less, p5 / (p3+p4) is 1.1 / 3 or more and 2 / 3 or less, and (valence of Li)×p1+(valence of the element D)×p2+(valence of La)×p3+(valence of the element E)×p4+(valence of the element Q)×p5+(valence of the metal element J)×p6=24 is satisfied.
2. 2. The Li ion conductor according to claim 1, having a lattice constant of 12.95 Å or more.
3. 3. The Li ion conductor according to claim 1, wherein p1 is 8.1 or more and 9.5 or less, p2, p4, and p6 are all 0 or more and 0.5 or less, p3 is 2.5 or more and 3 or less, and p5 is 1.5 or more and 2 or less.
4. Formula (2): Li x1 La x2 (Ga, V, Al) x3 Hf x4 Sr x5 Zr x6 O 12 A Li ion conductor represented by the formula: In formula (2), x1 is 8.1 or more and 9.5 or less, x2 is 2.5 or more and 3 or less, x3 is 1.5 or more and 2 or less, x4, x5, and x6 are each independently 0 or more and 0.5 or less, and x1 + x2 × 3 + x3 × 3 + x4 × 4 + x5 × 2 + x6 × 4 = 24 is satisfied, and (Ga, V, Al) means that at least one of Ga, V, and Al is contained, and when multiple types are contained, x3 means the total amount of the multiple types.
5. A raw material mixture containing at least one selected from group Q consisting of Ga, V, and Al, Li, La, and, as necessary, at least one of metal elements D, E, and J, wherein the molar ratio of each metal element in the raw material mixture is a stoichiometric ratio in a compound represented by formula (1): (Li p1 D p2 ) (La p3 E p4 ) (Q p5 J p6 ) O 12 , (In the above formula (1), Q is at least one element selected from the group consisting of Ga, V, and Al, D is a metal element that substitutes a part of the Li site, E is a metal element that substitutes a part of the La site, and J is a metal element that substitutes a part of the Q site; p1, p3, and p5 are values greater than 0, p2, p4, and p6 may be 0, p1 / (p3+p4+p5+p6) is 8.1 / 5 or more and 9.5 / 5 or less, p5 / (p3+p4) is 1.1 / 3 or more and 2 / 3 or less, and (valence of Li)×p1+(valence of the element D)×p2+(valence of La)×p3+(valence of the element E)×p4+(valence of the element Q)×p5+(valence of the metal element J)×p6=24 is satisfied. A method for producing a Li ion conductor, comprising firing at 1100° C. or higher.
Citation Information
Patent Citations
Lithium ion-conductive oxide and method of manufacturing the same
JP2013184848A
Method for manufacturing composite laminate, composite laminate and lithium battery
JP2016015213A
Lithium ion conductor and lithium ion battery using the same
JP2017091910A
High ion conductive solid electrolyte for all-solid state battery and method for preparing same
WO2018093059A1